Nanocrystalline ZnO: A Competent and Reusable Catalyst for the Preparation of Pharmacology Relevant Heterocycles in the Aqueous Medium - Saha, Moumita; Das, Asish R. (Current Green Chemistry, 2020)
Nanoparticle catalyzed synthesis is a green and convenient method to achieve most of the chemical transformations in water or other green solvents. Nanoparticle ensures an easy isolation process of catalyst as well as products from the reaction mixture avoiding the hectic work up procedure. Zinc oxide is a biocompatible, environmentally benign and economically viable nanocatalyst with effectivity comparable to the other metal nanocatalyst employed in several reaction strategies. This review mainly focuses on the recent applications of zinc oxide in the synthesis of biologically important heterocyclic molecules under sustainable reaction conditions. Application of zinc oxide in organic synthesis: Considering the achievable advantages of this nanocatalyst, presently several research groups are paying attention in anchoring zincoxide or its modified structure in several types of organic conversions e.g. multicomponent reactions, ligand-free coupling reactions, cycloaddition reaction, etc. The advantages and limitations of this nanocatalyst are also demonstrated. The present study aims to highlight the recent multifaceted applications of ZnO towards the synthesis of diverse heterocyclic motifs. Being a promising biocompatible nanoparticle, this catalyst has an important contribution in the fields of synthetic chemistry and medicinal chemistry.
Keywords: Bioactive heterocycles